The Analysis and Forecasting on Foreign Direct Investment, Tourism and Economic Growth in ASEAN Countries - Shuang Liu (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research analyzes and forecasts the relationship between foreign direct investment (FDI), tourism and economic growth (GDP) in Thailand, Singapore, Indonesia, Malaysia, Vietnam and Philippines, that countries with a high level of international tourism arrivals (ITA) and FDI in their economies. Based on the VAR model, the quarterly data for the period 2005 to 2019 are studied with two complementary methods of granger causality test and impulse response functions. All countries except Singapore and Malaysia is found granger causality from variables GDP to ITA, and the relationship shows negative impulse response. All countries except Thailand and Malaysia is obtained granger causality from variables FDI to ITA, and the relationship shows positive impulse response. All countries except Vietnam and Malaysia has granger causality from variables ITA to GDP, and the relationship exhibits positive and negative impulse response. The granger causality from variables GDP to FDI is obtained only in Malaysia, and the relationship exhibits positive impulse response. The granger causality from variables FDI to GDP is found only in Singapore, and the relationship exhibits positive and negative impulse response in different period. Besides, the causality from variables ITA to FDI is not found in the countries of research samples.